MANAJEMEN STRATEGI PIMPINAN PONDOK DALAM PEMBINAAN SANTRI PONDOK PESANTREN AN-NURIYAH BONTOCINI DI KABUPATEN JENEPONTO (Fakultas Dakwah dan Komunikasi, 2020)
The purpose of this research is to study How the Management Strategy of Pondok Leaders in the Development of An-Nuriyah Bontocini Islamic Boarding School Students in Jeneponto Regency. The type of research used is descriptive qualitative by preaching management. Data sources used are primary and secondary data sources. Data collection uses observation, interviews and documentation. An-Nuriyah Bontocini is a family management system and open management. While the strategy of the leaders of the pondok in guidance to students is to make programs or activities. Like 1) Tahfidzul Quran, done in a way that is one day one verse and students are accustomed to reading the Koran one page after the midday prayer. 2) Book readers, every santri interviewed has 24 books. 3) Strengthening Foreign Languages (English, Arabic, French, Mandarin and Japanese). 4) Da'wah training is carried out in ways such as duha prayer, midday prayer, seven-minute lecture, Tamrinul Khitaba, and Ramadan Safari. 5) Carry out extracurricular activities such as Boy Scouts, Karate, KKS and Art Studio, and also Intra School Santri Organization. 6) Annual activities such as opening together, maulid, qurban and milad.